2021
DOI: 10.5802/crmeca.74
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid piezoelectric–electromagnetic nonlinear vibration energy harvester excited by fluid flow

Abstract: Energy harvesting mechanisms can be used to extract energy from ambient surroundings to power small electronic devices, which has a significant advantage in realizing self-sustaining wireless devices. The proposed design of this study uses the internal fluid flow within a pipe and takes advantage of the fluidstructure interaction through flow-induced vibration of a bluff body. The hybrid harvester uses the vibration to convert electrical energy through a piezoelectric material and an electromagnetic oscillator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…• Vorticity varied with the bluff body shapes. Ellipse and isosceles triangle-shaped bluff body performed best during resonance in a frequency study with finite element modelling methods [3].…”
Section: Resultsmentioning
confidence: 99%
“…• Vorticity varied with the bluff body shapes. Ellipse and isosceles triangle-shaped bluff body performed best during resonance in a frequency study with finite element modelling methods [3].…”
Section: Resultsmentioning
confidence: 99%
“…The work demonstrated that maximum power output and efficiency from a hybrid PE system was greater than traditional piezoelectric or electromagnetic energy harvesters and more power can be harvested from the electromagnetic than the piezoelectric system. Hafizh et al (2021) investigated the bluff body optimization parameters for resonant vibration under fluid flow for a hybrid piezoelectric-electromagnetic system. The proposed hybrid harvester departs from previous work by utilizing a vertical harvester with an internal electromagnetic compact geometry that is fully submerged in water under the influence of VIV.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main advantages of piezoelectric-based devices are the simple nature of piezoelectric transducers, which enable designers to use a simple mechanism in the harvester, in addition to their durability, high voltage, high impedance of output, and high energy production density [ 25 , 26 ]. Some vibrational energy converters use a combination of the aforementioned transducers to reach a higher conversion efficiency [ 27 ].…”
Section: Introductionmentioning
confidence: 99%